Quantization of Lyapunov functions - Sharko, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
For a state of equilibrium of an autonomous system of differential equations, we propose discrete conditions for stability and asymptotic stability in the sense of Lyapunov.